Исследование влияния угла атаки потока на показания напорного усилителя - Беляев Л. А. Леонид Александрович; Брагин В. А.; Калугин Б. Ф. Борис Федорович; Коновалов И. Н. (1975, 1975)
Заглавие с титульного листа